The Correlation of Students’ Reading Interest, Vocabulary Mastery and Their Reading Comprehension (Program Studi Magister Tadris Bahasa Inggris UIN Sultan Maulana Hasanuddin Banten, 2022)
The study is aimed to find out The Correlation of Students’ Reading Interest, Vocabulary Mastery and Their Reading Comprehension at Tenth Grade of SMA Paradigma. The method of the research used quantitative research. The population was 175 students and 40 students as a sample. The result showed that (1) There is no positive significant correlation between students’ reading interest and their reading comprehension at SMA Paradigma Kabupaten Tangerang in Academic Year 2020/2021. With the value t_count < t_table (1,238 < 1,687). (2) There is positive significant correlation between students’ vocabulary mastery and their reading comprehesion at tenth grade of SMA Paradigma Kabupaten Tangerang in academic year 2020/2021. The result of the variable students’ vocabulary mastery is 2,473 which means t_count > t_table (2,473 > 1,687). (3) There is a positive simultaneous correlation of students’ reading interest, vocabulary mastery and their reading comprehension at tenth grade of SMA Paradigma Kabupaten Tangerang in academic year 2020/2021. The result of students’ reading interest and vocabulary mastery on their reading comprehension with a significance value of 0,005 < 0,05 it can be concluded that the greater the interest in reading, the greater their vocabulary mastery, and automatically students will have a good reading comprehension.